Aligning Policy, Place and Public Value: Planning Age Friendly Cities in Municipal Organizations. Issue 2 (4th March 2022) - Keyes, Laura; Collins, Brian; Tao, Jie; Tiwari, Chetan
ABSTRACT: Municipalities are important to age-friendly policy implementation and need to be engaged to bring about the desired physical changes and community supports. As a governing unit, municipalities can allocate resources and leverage their capacity by acting in certain ways. As a planning process, age-friendly policies should be embedded in all levels of municipal government to ensure that maximum public benefits can be leveraged. Three strategies effectively illustrate the opportunity toward internal municipal collaboration: analytic mapping enables policy makers to visualize the captured value of public amenities; policy mapping reveals where departments are reinforcing or contradicting age-friendly policy actions; and effective advocacy builds public support and guides municipal agenda setting. San Antonio, Texas, provides a context to illustrate how the strategies can be implemented to further the goal of age-friendly planning as demonstrated through their commitment and designation as an AARP Age-Friendly Community. This replicable framework will help cities pursing age-friendly policy action to forge connections across departments, policy makers, community partners, and the public toward broader policy implementation. Key Points: Age-friendly planning should not fall to local departments of senior services only. Planning coordination of age-friendly policy results in more diverse outcomes. Mapping is a tool helping policy makers visualize alternative opportunities. Maps give stakeholders the ability to track and monitor progress. This approach is easily replicable for cities implementing age-friendly programs.